Effect of UMMB (urea molasses multi-nutrient block) based on coffee skin on erythrocytes, hematocrit and hemoglobin in transport stress of sheep - Sri Ruwandani; Yunilas; Ade Trisna (Talenta Publisher, 2024)
Transportation stress in livestock can be caused by distance and travel time, crowding in the transport vehicle, malnutrition during transportation, climatic conditions, lack of availability of food and drink and lack of handling during travel. The aim of providing coffee peel-based UMMB is to overcome nutritional deficiencies and stress in livestock during transportation. This research was carried out experimentally with a non-factorial completely randomized design (CRD) with 4 treatments K0 (without UMMB) as control, K1 (UMMB based on 10% fermented coffee peel), K2 (UMMB based on 20% coffee peel), K3 (UMMB based on fermented coffee peel 30%) and 4 repetitions. The research parameters are erythrocytes, hematocrit and hemoglobin. The results showed that administration of UMMB based on fermented coffee peel had a significant effect (P<0.05) on reducing erythrocyte levels (16.58%), decreasing hematocrit levels (18.30%) and decreasing hemoglobin levels (31.72%). The conclusion of this research is that administering coffee peel-based UMMB at a dose of 30% can reduce erythrocyte, hematocrit and hemoglobin levels in sheep transportation stress